O31 IL-27 regulates the magnitude of ectopic germinal centres in experimental sialadenitis but fails to modulate IL-17 and IFNg production in CD4 T cells from patients with Sjögren's syndrome. (20th April 2020) - Lucchesi, Davide; Coleby, Rachel; Pontarini, Elena; Prediletto, Edoardo; Rivellese, Felice; Hill, David; Soria, Alicia Derrac; Jones, Simon; Humphreys, Ian; Sutcliffe, Nurhan; Tappuni, Anwar; Pitzalis, Costantino; et al.
Abstract: Background: A third of Sjögren's syndrome (SS) patients develop ectopic lymphoid structures (ELS) in their salivary glands (SG). ELS play an active role in autoimmunity and contribute to the development of MALT lymphoma. Interleukin 27 (IL-27) exerts key immunomodulatory actions on numerous immune cells but its role in the formation and regulation of ELS in the SG of SS is unknown. Here we used a murine model of SG ELS to elucidate the role of IL-27 and its interaction with IL-17 in the development, regulation and function of ELS. We extended our observations on a cohort of SS patients to identify IL-27 cellular source, target cells and functional properties in modulating CD4 T cells function. Methods: A single dose of reporter-encoding adenovirus was delivered directly to the SG of wild-type (WT) and IL-27RA-deficient (KO) mice to trigger ELS formation. For IL-17 blockade, anti-mouse IL-17A antibody was used. ELS development and peripheral immune responses were tracked by immuno-histopathology, FACS, and qPCR. Minor SG biopsies were collected from SS and non-specific sialadenitis (sicca) patients. Peripheral blood mononuclear cells (PBMC) isolated from SS and rheumatoid arthritis (RA) patients and age/sex-matched healthy donors (HD). For in vitro experiments PBMCs were incubated with IL-27 and analysed by FACS and cytokines levels were measured in culture supernatants. Tissue IL-27 was assessed by multicolour immunofluorescence. Results: In WT mice, SG ELS formation was preceded by upregulation of IL-27p28 and infiltration of IL-27 producing cells. KO mice displayed larger, more abundant ELS in the SG. Higher expression levels of ELS-related genes ( Cxcl13, Ccl19, Ltb, Aid ) compared to WT mice were measured. KO mice showed an uncontrolled SG Th17 response and systemic IL-17A blockade caused a reduction in ELS size and in the expression of ELS-related genes. In SS patients SG and serum, we observed higher expression levels of IL-27 transcripts and protein, compared to sicca. SG IL-27 was selectively increased in ELS+ patients. IL-27 staining was detected in the T cell-rich areas of SG ELS often co-localizing with DC-LAMP+ dendritic cells. While IL-27 was able to significantly downregulate IL-17 production in HD and RA, CD4 T cells from patients with SS failed to downregulate IL-17 but showed an aberrant IFNγ release upon IL-27 incubation. Conclusion: The IL-27-mediated restriction of Th17 expansion plays a critical role in the regulation of germinal centre response. Both in murine inducible ELS and in patients with SS, dendritic cells appear as the main cellular source of IL-27. IL-27 consistently failed to downregulate IL-17 release in CD4 T cells from SS patients, albeit its expression was increased in the ELS+ subset of SS, suggesting that a profound dysregulation of the IL-27/IL-17 axis play an important role in ELS formation in this condition. Disclosures: D. Lucchesi None. R. Coleby None. E. Pontarini None. E. Prediletto None. F. Rivellese None. D. Hill None. A. Derrac Soria None. S. Jones None. I. Humphreys None. N. Sutcliffe None. A. Tappuni None. C. Pitzalis None. G. Jones None. M. Bombardieri None.